Mechanical Thrombectomy Quality Indicators Study in Czech Stroke Centers: Results of the METRICS Study - Köcher, Martin; Šaňák, Daniel; Zapletalová, Jana; Cihlář, Filip; Czerny, Daniel; Černík, David; Duras, Petr; Fiksa, Jan; Hustý, Jakub; Jurák, Lubomír; Kovář, Martin; Lacman, Jiří; et al. (Journal of stroke and cerebrovascular diseases, 2022)
BACKGROUND AND PURPOSE: Rigorous and regular evaluation of defined quality indicators is crucial for further improvement of both technical and clinical results after mechanical thrombectomy (MT) for acute ischemic stroke (AIS). Following the recent international multi-society consensus quality indicators, we aimed to assess trend in these indicators on national level. MATERIAL AND METHODS: The prospective multicenter study (METRICS) was conducted in Czech Republic (CR) in year 2019. All participating centers collected technical and clinical data including defined quality indicators and results were subsequently compared with those from year 2016. RESULTS: In the 2019, 1375 MT were performed in the CR and 1178 (86%) patients (50.3% males, mean age 70.5 ± 13.0 years) were analyzed. Recanalization (TICI 2b-3) was achieved in 83.7% of patients and 46.2% of patients had good 3-month clinical outcome. Following time intervals were shortened in comparison to 2016: "hospital arrival - GP" (77 vs. 53 min; p<0.0001), "hospital arrival - maximal achieved recanalization" (122 vs. 93 min; p<0.0001), and "stroke onset - maximal achieved recanalization" (240 vs. 229 min; p p<0.0001). More patients with tandem occlusion were treated in 2019 (7.8 vs. 16.5%; p<0.0001) and more secondary transports were in 2019 (31.3 vs. 37.8%; p=0.002). No difference was found in 3-month clinical outcome and in the rate of periprocedural complications. Results of the METRICS study met all criteria of multi-society consensus quality indicators. CONCLUSION: Nationwide comparison between 2016 and 2019 showed improvement in the key time intervals, but without better overall clinical outcomes after MT.
Keywords: Brain Ischemia; mužské pohlaví; Retrospective Studies; Male; Czech Republic; senioři; senioři nad 80 let; retrospektivní studie; cévní mozková příhoda; výsledek terapie; Ischemic Stroke; Thrombectomy; Female; Humans; trombektomie; ischemická cévní mozková příhoda; ischemie mozku; lidé; Benchmarking; Prospective Studies; ukazatele kvality zdravotní péče; ženské pohlaví; lidé středního věku; Middle Aged; Česká republika; Stroke; Aged, 80 and over; Quality Indicators, Health Care; Treatment Outcome; prospektivní studie; benchmarking; Aged